2020
DOI: 10.1007/s11060-020-03555-z
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid circulating tumor cells as a quantifiable measurement of leptomeningeal metastases in patients with HER2 positive cancer

Abstract: Purpose The CellSearch® system has been used to identify circulating tumor cells (CTCs) in cerebrospinal fluid (CSF) to diagnose leptomeningeal metastasis (LM) in patients with epithelial cancers. Using this system, we prospectively explored sequential CSF CTC enumeration in patients with LM from HER2+ cancers receiving intrathecal (IT) trastuzumab to capture dynamic changes in CSF CTC enumeration. Methods CSF from patients enrolled in an IRB-approved phase I/II dose escalation trial of IT trastuzumab for LM i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(38 citation statements)
references
References 23 publications
1
37
0
Order By: Relevance
“…Several groups have developed flow cytometry-based approaches for the detection of breast cancer LM, capturing cells positive for tumor cell specific markers from CSF [ 53 , 54 , 55 ]. Others have applied rare cell capture technologies to standard CSF cytology approaches to improve the detection sensitivity of tumor cells [ 56 , 57 , 58 , 59 ]. Approaches examining the genome, transcriptome, proteome, or miRNAs found in CSF may also hold future promise in diagnosing LM [ 37 , 60 , 61 , 62 ].…”
Section: Diagnosis Of Lmmentioning
confidence: 99%
“…Several groups have developed flow cytometry-based approaches for the detection of breast cancer LM, capturing cells positive for tumor cell specific markers from CSF [ 53 , 54 , 55 ]. Others have applied rare cell capture technologies to standard CSF cytology approaches to improve the detection sensitivity of tumor cells [ 56 , 57 , 58 , 59 ]. Approaches examining the genome, transcriptome, proteome, or miRNAs found in CSF may also hold future promise in diagnosing LM [ 37 , 60 , 61 , 62 ].…”
Section: Diagnosis Of Lmmentioning
confidence: 99%
“…In patients with LM secondary to breast cancer receiving intrathecal trastuzumab, a decreased number of CTCs was reported in those responding to treatment. 22 The study also reported increased CTCs in three patients approximately one month prior to clinical signs of progression. 22 These early findings suggest CTCs could provide quantitative measures of response, recurrence, and progression.…”
Section: Diagnostic Advances In Leptomeningeal Metastasismentioning
confidence: 77%
“… 22 The study also reported increased CTCs in three patients approximately one month prior to clinical signs of progression. 22 These early findings suggest CTCs could provide quantitative measures of response, recurrence, and progression. CSF CTCs may also have a prognostic significance: increased serum CTCs portend a worse prognosis in solid tumors 23 ; changes in the number of CSF CTCs on serial sampling may similarly predict prognosis, providing essential information for risk stratification, and treatment planning.…”
Section: Diagnostic Advances In Leptomeningeal Metastasismentioning
confidence: 77%
“…It has to be noticed, that even if most of the studies on CTCs uses blood as biological sample, also other fluids may be useful. A recent study by Malani et al reports the identification of CTCs in the cerebrospinal fluid of BC patients with leptomeningeal metastases [102]. This finding will open the way to further studies to assess the clinical relevance of specific body fluids evaluation to stratify MBC patients.…”
Section: Clinical Application Of Liquid Biopsy Breast Cancermentioning
confidence: 83%